MINOR ELEMENT PARTITIONING AND SECTOR ZONING IN SYNTHETIC AND METEORITIC ANORTHITE - Steele I.M.; Peters M.T.; Shaffer E.E.; Burnett D.S. (My University, 1997)
Regular, geometric, apparently crystallographically-controlled, sector zoning has been produced in synthetic anorthite crystallized from a liquid of Type B Ca,Al-rich inclusion (CAI) composition. Cathodoluminescence (CL) provides a rapid method for observing the sectors. Sharp discontinuities in Mg concentration always accompany sharp changes in CL intensity at sector boundaries. Although CL intensity anti-correlates with Mg concentration, there is not a well-defined quantitative relationship, and Mg concentration steps range from as little as 5% to almost a factor of 2 for different CL boundaries. When measurable, Na also tends to anti-correlate with CL brightness in a given crystal and thus correlates with Mg. The partition coefficients for Mg and Na can vary by up to a factor of 2 depending on the particular sector and thus are not constant for CAI anorthite which formed by fractional crystallization. In contrast, Ti (either Ti+3 or Ti+4) concentration is not a function of sector zoning and thus does not affect the CL intensity.The sector zoning and correlated chemical variations for synthetic anorthite are similar to those in natural anorthite from Type B CAIs. The CL intensity, boundary sharpness, and minor element zoning in synthetic anorthite are not affected by annealing at 850°C for three weeks. Overall, our observations suggest that the observed CL patterns and minor element zoning in Type B anorthite are igneous in origin and have not been modified by subsolidus reequilibration or alteration. This leads to the conclusion that the 26Mg-26Al systematics in CAIs (based almost entirely on anorthite) have not been modified by subsolidus reequilibration or alteration.